Структура содержания прямых (номинативных) значений прилагательных вкуса - Лечицкая, Ж.В. (Kalbotyra, 1985)
The present article is an attempt to study the dictionary entries of adjectives denoting “taste”. The semantic components forming the meaning of the adjectives denoting “taste” are binary, gradual, frequentative oppositions as well as elementary components. The content of the meanings formed by the adjectives denoting “taste” is characterized by the intensity of quality and emotive-evaluative charge. The linguistic content of the adjectives is comprehended and represented with regard to the presence or absence of the quality, their dynamic character and the emotional response of the perceiver.